Kubernetes : up and running: dive into the future of infrastructure - Hightower, Kelsey; Burns, Brendan; Beda, Joe (O'Reilly Media, 2017)
Legend has it that Google deploys over two billion application containers a week. How's that possible? Google revealed the secret through a project called Kubernetes, an open source cluster orchestrator (based on its internal Borg system) that radically simplifies the task of building, deploying, and maintaining scalable distributed systems in the cloud. This practical guide shows you how Kubernetes and container technology can help you achieve new levels of velocity, agility, reliability, and efficiency. Authors Kelsey Hightower, Brendan Burns, and Joe Beda--who've worked on Kubernetes at Google and other organizatons--explain how this system fits into the lifecycle of a distributed application. You will learn how to use tools and APIs to automate scalable distributed systems, whether it is for online services, machine-learning applications, or a cluster of Raspberry Pi computers.- Explore the distributed system challenges that Kubernetes addresses- Dive into containerized application development, using containers such as Docker- Create and run containers on Kubernetes, using the docker image format and container runtime- Explore specialized objects essential for running applications in production- Reliably roll out new software versions without downtime or errors- Get examples of how to develop and deploy real-world applications in Kubernetes.